Contact Force Measurements in Cam and Follower Lubricated Contacts - Ciulli, Enrico; Fazzolari, Francesco; Pugliese, Giovanni (Frontiers in Mechanical Engineering, 2020)
Cam-follower contacts are characterized by continuous changes of operating parameters such as speed, load and geometry, so that both numerical simulations and experimental measurements are very complex. An experimental apparatus has been specifically designed and realized to perform tests with cam–follower pairs. The apparatus allows measurements of contact forces with a custom-made dynamometer and of lubricant film thickness and shape with optical interferometry. After an introductory review of experimental works on cam-follower pairs mainly related to force measurements, the test rig used for the experimental work reported in the paper is briefly described. Some trends of all components of the contact forces measured during the rotation of a circular eccentric cam and an engine spline cam are presented. Tests have been performed at different rotational speeds and preloads. The friction trends can be associated to mixed and boundary lubrication regimes. Some unattended friction peaks are found in tests with the spline cam and possible explanations are given.